Second opinions for spinal surgery: a scoping review - Giovanni E. Ferreira; Joshua Zadro; Chang Liu; Ian A. Harris; Chris G. Maher (BMC Health Services Research, 2022)
Abstract Background Second opinions have the goal of clarifying uncertainties around diagnosis or management, particularly when healthcare decisions are complex, unpleasant, and carry considerable risks. Second opinions might be particularly useful for people recommended surgery for their back pain as surgery has at best a limited role in the management of back pain. Methods We conducted a scoping review. Two independent researchers screened PubMed, EMBASE, Cochrane CENTRAL and CINAHL from inception to May 6th, 2021. Studies of any design published in any language were eligible provided they described a second opinion intervention for people with spinal pain (low back or neck pain with or without radicular pain) either considering surgery or to whom surgery had been recommended. We assessed the methodological quality with the Downs & Black scale. Outcomes were: i) characteristics of second opinion services for people considering or who have been recommended spinal surgery, ii) agreement between first and second opinions in terms of diagnoses, need for surgery and type of surgery, iii) whether they reduce surgery and improve patient outcomes; and iv) the costs and healthcare use associated with these services. Outcomes were presented descriptively. Results We screened 6341 records, read 27 full-texts, and included 12 studies (all observational; 11 had poor methodological quality; one had fair). Studies described patient, doctor, and insurance-initiated second opinion services. Diagnostic agreement between first and second opinions varied from 53 to 96%. Agreement for need for surgery between first and second opinions ranged from 0 to 83%. Second opinion services may reduce surgery rates in the short-term, but it is unclear whether these reductions are sustained in the long-term or if patients only delay surgery. Second opinion services may reduce costs and healthcare use (e.g. imaging), but might increase others (e.g. injections). Conclusions Second opinion services typically recommend less surgical treatments compared to first opinions and may reduce surgery rates in the short-term, but it is unclear whether these reductions are sustained in the long-term or if patients only delay surgery. There is a need for high-quality randomised trials to determine the value of second opinion services for reducing spinal surgery.